A pilot study to compare daily with twice weekly transcutaneous posterior tibial nerve stimulation for faecal incontinence. (December 2013) - Thomas, G. P.; Dudding, T. C.; Bradshaw, E.; Nicholls, R. J.; Vaizey, C. J.
Abstract Aim Posterior tibial nerve stimulation (PTNS) has been shown to improve faecal incontinence in the short term. The optimal treatment regimen is unclear with wide variations in protocol reported in the literature. The study aimed to assess two different regimens of transcutaneous PTNS and to establish whether increasing the frequency of stimulation increases the effectiveness. Method Thirty patients were randomized to receive once daily or twice weekly PTNS for a 6‐week period. The treatment was carried out by the patient at home after instruction. The primary investigator was blinded to the patient allocation until the study had ended, at which point the symptoms were assessed. No further stimulation was given after 6 weeks and the patients were followed until their symptoms returned to the pre‐stimulation state (baseline). The primary outcome measure was a change in the frequency of incontinent episodes. Results Three patients in the daily group and none in the twice weekly group achieved complete continence. Only patients from the daily group showed a significant reduction in median (interquartile range) incontinent episodes per week from 5 (11.13) to 3.5 (4.31) (P = 0.025). There was no significant change in the frequency of defaecation nor in the ability to defer defaecation. Patients in the daily group experienced a significant improvement in the domains of lifestyle [2.2 (1.7) to 2.6 (1.65), P = 0.04] and embarrassment [1.7 (0.85) to 2.15 (0.4), P = 0.04] on the Rockwood Fecal Incontinence Quality of Life assessment. No adverse events were reported. Conclusion Transcutaneous PTNS can safely be used by the patient at home. Daily treatment may be more effective than twice weekly treatment. Larger studies are needed to investigate this further.